2013
DOI: 10.1111/wrr.12136
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin inhibits transforming growth factor‐β1‐induced expression of type I collagen, CTGF, and α‐SMA in keloid fibroblasts

Abstract: Simvastatin, a 3-hydroxy-3-methylglutaryl coenzyme-A reductase inhibitor, is used to reduce cholesterol levels. Accumulating evidence has revealed the immunomodulatory and anti-inflammatory effects of simvastatin that prevent cardiovascular diseases. In addition, the beneficial effects of statins on fibrosis of various organs have been reported. However, the functional effect of statins on dermal fibrosis of keloids has not yet been explored. The objective of this study was to determine whether simvastatin cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 42 publications
4
48
1
Order By: Relevance
“…40 After injury, it continues to rise steadily through day 40, and blockade of CTGF mRNA by antisense oligonucleotides is associated with reduction of collagen types I and III and scarring. 35 Our results indicate that the scar reduction effect of statins is at least partly due to the decrease of CTGF expression, and consequently the decrease of collagen expression, which is consistent with Mun et al’s 41 in vitro study and Watts and Spiteri’s 12 in vivo study. Whether statin affected the expression of TGF-βRII is unclear in this study.…”
Section: Discussionsupporting
confidence: 90%
“…40 After injury, it continues to rise steadily through day 40, and blockade of CTGF mRNA by antisense oligonucleotides is associated with reduction of collagen types I and III and scarring. 35 Our results indicate that the scar reduction effect of statins is at least partly due to the decrease of CTGF expression, and consequently the decrease of collagen expression, which is consistent with Mun et al’s 41 in vitro study and Watts and Spiteri’s 12 in vivo study. Whether statin affected the expression of TGF-βRII is unclear in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this finding, there was a decrease in type I collagen expression of similar magnitude. In addition to directly downregulating type I collagen expression 29 , simvastatin can also indirectly regulate the ECM content of tissues by modulating MMP expression and activity levels. Aktas and colleagues 2 reported that simvastatin reduced the levels of MMP-3 in articular chondrocytes after induction of an ACL tear, and Yao 42 reported simvastatin decreased MMP-9 expression in the vasculature of rats with experimentally induced pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthetic pathway of collagen production is a very complex (Mun et al , 2014). Specific collagens are encoded by specific genes; COL1A1 an COL1A2 for type I collagen and COL3A1 for type III collagen, are may involve in the regulation of collagen synthesis in animal (Gonzalez et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The collagen biosynthesis is very complex; about 34 genes are involved in collagen formation. The cytokine and growth factors genes are involved to synthesis of both type I and type III collagen through phosphorylation of the downstream mediators, Smad2/3in fibroblasts (Mun et al , 2014). Other than this, apoptotic and heat shock proteins/genes are also involved in collagen synthesis has been unclear (Alikhani et al , 2005).…”
Section: Introductionmentioning
confidence: 99%